Analgesic Effects of Intra-Articular Bupivacaine/Intravenous Parecoxib Combination Therapy versus Intravenous Parecoxib Monotherapy in Patients Receiving Total Knee Arthroplasty: A Randomized, Double-Blind Trial. (11th June 2015) - Shen, Shih-Jyun; Peng, Pei-Yu; Chen, Hsiu-Pin; Lin, Jr-Rung; Lee, Mel S.; Yu, Huang-Ping
Abstract : Objectives . The purpose of this double-blind, randomized study was to investigate whether the addition of intra-articular bupivacaine to intravenous parecoxib could improve pain relief in patients undergoing total knee arthroplasty. Methods . A total of 36 patients undergoing total knee arthroplasty were enrolled into our study. These patients were randomly allocated either to a placebo-controlled group or study group. Postoperative pain scores and analgesic consumption were evaluated. Results . Numeric rating scale (NRS) data of bupivacaine group in postoperative room were significantly lower than that of control group (control group versus bupivacaine group, 7.9 (6.7–9.1) (mean and 95% confidence interval) versus 4.5 (3.2–5.8) (mean and 95% confidence interval), p = 0.001 ). NRS data of bupivacaine group in ward were also significantly lower than that of control group. A significantly lower dose of meperidine was used in the study group postoperatively during the first 24 hours (control group versus bupivacaine group, 3.08 ± 0.80 mg/Kg versus 2.34 ± 0.42 mg/Kg, p = 0.001 ). Conclusion . Intra-articular bupivacaine in combination with intravenous parecoxib may improve pain relief and reduce the demand for rescue analgesics in patients undergoing total knee arthroplasty. The trial is registered with Australian New Zealand Clinical Trials Registry (ACTRN12615000463572 ).